Complexity Analysis of the Piece-Wise Affine Approximation for the Car on the Nonlinear Hill Model Related To Discrete–Time, Minimum Time Control Problem - Orlowski, P. (Elektronika ir Elektrotechnika, 2014)
The main aim of the paper is to analyse effectiveness of the approximation method from the nonlinear discretised into discrete piece-wise affine model. Accuracy and numerical complexity of the piece-wise affine control system grow with the number of polyhedral partitions, that describe the system. The model with state dependent nonlinearity can be effectively approximated by proposed secant piece-wise linear approximation. The effectiveness of the proposed method is evaluated on the car on the nonlinear hill model. DOI: http://dx.doi.org/10.5755/j01.eee.20.10.4454